Shear Behavior of One-Way Reinforced Concrete Hollow Slabs Voided with PET Void Formers - Hasan, Haider H. (2023)
A Master of Science thesis in Civil Engineering by Haider H. Hasan entitled, “Shear Behavior of One-Way Reinforced Concrete Hollow Slabs Voided with PET Void Formers”, submitted in May 2023. Thesis advisor is Dr. Sami Tabsh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).